Indirect effect of oral azithromycin on the gut resistome of untreated children: a randomized controlled trial. Issue 2 (17th June 2020) - Oldenburg, Catherine E; Hinterwirth, Armin; Worden, Lee; Sié, Ali; Dah, Clarisse; Ouermi, Lucienne; Coulibaly, Boubacar; Zhong, Lina; Chen, Cindi; Ruder, Kevin; Lietman, Thomas M; Keenan, Jeremy D; et al.
Abstract: Background: Antibiotic use by one individual may affect selection for antimicrobial resistance in close contacts. Here we evaluated whether oral antibiotic treatment of one child within a household affected the gut resistome of an untreated cohabiting child. Methods: Households with at least two children <5 y of age were randomized in a 1:1 fashion to a 5d course of azithromycin or placebo. To evaluate indirect effects of azithromycin treatment on the gut resistome, we randomly assigned one child in the house to azithromycin and one to placebo. In placebo households, each child received placebo. We performed DNA sequencing of rectal swabs collected 5 d after the last antibiotic dose. We estimated risk ratios for the presence of genetic resistance determinants at the class level using modified Poisson models for children in azithromycin households compared with placebo households and assessed the composition of the resistome using permutational analysis of variance (PERMANOVA). Results: Of 58 children (n = 30 azithromycin households, n = 28 placebo households) with post-treatment rectal swabs, genetic resistance determinants were common but there was no significant difference at the class (p = 0.54 for macrolides) or gene (p = 0.94 for structure by PERMANOVA, p = 0.94 for diversity) level between untreated children in azithromycin households compared with placebo households. Conclusions: The results are encouraging that one child's antibiotic use may not influence the resistome of another child. Trial registration: ClinicalTrials.gov NCT03187834.